Responses of Mytilus galloprovincialis to challenge with the emerging marine pathogen Vibrio coralliilyticus. Issue 84 (January 2019) - Balbi, Teresa; Auguste, Manon; Cortese, Katia; Montagna, Michele; Borello, Alessio; Pruzzo, Carla; Vezzulli, Luigi; Canesi, Laura
Abstract: Vibrio coralliilyticus has emerged as a coral pathogen of concern throughout the Indo-Pacific reef. The interest towards understanding its ecology and pathogenic potential has increased since V. coralliilyticus was shown to be strongly virulent also for other species; in particular, it represents a serious threat for bivalve aquaculture, being one of the most important emerging pathogen responsible for oyster larval mortalities worldwide. V. coralliilyticus has a tightly regulated temperature-dependent virulence and it has been related to mass mortalities events of benthic invertebrates also in the temperate northwestern Mediterranean Sea. However, no data are available on the effects of V. coralliilyticus in the mussel Mytilus galloprovincialis, the most abundant aquacultured species in this area. In this work, responses of M. galloprovincialis to challenge with V. coralliilyticus (ATCC BAA-450) were investigated. In vitro, short term responses of mussel hemocytes were evaluated in terms of lysosomal membrane stability, bactericidal activity, lysozyme release, ROS and NO production, and ultrastructural changes, evaluated by TEM. In vivo, hemolymph parameters were measured in mussels challenged with V. coralliilyticus at 24h p.i. Moreover, the effects of V. coralliilyticus on mussel early embryo development (at 48 hpf) were evaluated. The results show that both in vitro and in vivo, mussels were unable to activate immune response towards V. coralliilyticus, and that challenge mainly induced lysosomal stress in the hemocytes. Moreover, V. coralliilyticus showed a strong and concentration-dependent embryotoxicity. Overall, the results indicate that, although M. galloprovincialis is considered a resistant species to vibrio infections, the emerging pathogen V. coralliilyticus can represent a potential threat to mussel aquaculture. Graphical abstract: Highlights: Evaluation of Mytilus immune responses to the emerging pathogen V. coralliilyticus . In vitro and in vivo responses and developmental effects were measured. Hemocyte lysosomal stress was observed, but no induction of immune parameters. Strong and concentration-dependent effects on embryo development. Mytilus is unable to mount an efficient immune response towards V. coralliilyticus .